Hubungan antara pengurusan program latihan dan kepimpinan transformasional dengan kepuasan atlet: inovasi sukan sebagai pengantara - Siti Nur Ain, Zakinuddin (2021)
Management is a required skill in any field. Effective management will make an organization more competent and better functioning. One of the elements of management that is increasingly seen as important is innovation. Innovation is an element that is becoming increasingly important, even in sports organizations. The importance of innovation is seen as more and more evident as technology advances. Moreover, athlete satisfaction is considered as a kind of subjective characteristic that cannot be judged by the naked eye. This study addresses the role of sport innovation as a mediator between training program management, transformational leadership, and athlete satisfaction. Athletes registered with National Sports Council participated in this quantitative study. The software system Statistical Package for the Social Sciences (SPSS) 25 and Partial Least Squares Structural Equation Modeling (PLS-SEM) version 3 were used to analyze the data. The results show that there is a significant relationship between training program management and athlete satisfaction. However, there is no significant relationship between transformational leadership and athlete satisfaction. It was found that the mediating variable sport innovation does not act as a mediator for the relationship between training program management and athlete satisfaction. Yet, sport innovation is able to mediate the relationship between transformational leadership and athlete satisfaction. The findings of this study should help future researchers understand the impact of sport innovation on athlete satisfaction and provide clearer guidelines for managing training programs and transformational leadership in sport. The authors suggest that future studies use different variables and methods and focus on athletes under the age of 12 as respondents.